A study of serum calcium, phosphorous and magnesium level in hypothyroid cases - Arun Dhungana; Naveen Shreevastva; Subash Pant; Baburam Pokharel (Journal of Pathology of Nepal)
Background: Hypothyroidism is an endocrine disorder occurred either due to its impaired activity or hormonal deficiency. Trace elements are required as a cofactor for many enzymes in various metabolic pathways which are regulated by thyroid hormone. Hence, thyroid disorders are linked with disturbances in various metabolisms. So, the purpose of this study is to evaluate whether serum calcium, magnesium, and phosphorus level are deranged or not in hypothyroid cases.